Aflatoxin Contamination of Some Crop Seed Types and their Products in the Gezira State, Sudan - Abdel-Rahim, Awad M.; Alsheikh, Sahar M.; Suleiman, Abdel Moneim E. (Gezira Journal of Engineering and Applied Sciences, 2018)
The present study investigated the aflatoxin contamination levels as well as infection with A. flavus , in samples of groundnut collected from different areas in Gezira State. Aflatoxin contamination levels were at their minimum in samples collected from the villages (producing areas) compared to very high levels in samples collected from the main central markets in Wad Medani. However, samples collected from local markets in the producing areas were less contaminated. Moreover, the infection with A. flavus followed the same pattern of aflatoxin contamination with higher infection in samples collected from Wad Medani markets. Aflatoxin contamin-ation was high in groundnut seeds from insect damaged pods, while, the sound intact ones were almost free from aflatoxin. Regarding aflatoxin contamination of different groundnut seed products, the present study showed that grey and red roasted nuts were both highly contaminated. However, more aflatoxins accumulated when these nuts were sold in thin plastic bags. The legumes seeds (Phaseolus, Faba bean, and Chick pea) were highly contaminated with aflatoxins and also infected with A. flavus compared to the cereal seeds (wheat & sorghum). Seeds of crops other than the groundnut, collected from the two main markets of Wad Medani town, included both bagged and non- bagged samples. Seeds of these crops sold in thin plastic bags had higher levels of moisture content and also higher incidence of A. flavus as well as, large amounts of aflatoxins.